Dexmedetomidine for prevention of delirium in elderly patients after non-cardiac surgery - Karren, Elliott A.; King, Adam B.; Hughes, Christopher G. (Journal of Thoracic Disease; Vol 8, No 12 (December 31, 2016): Journal of Thoracic Disease, 2016)
Delirium is a common morbidity after surgery and in patients admitted to the intensive care unit (ICU). The development of delirium is associated with increased hospital costs, prolonged hospital stays, and increased in-hospital mortality (1-3). Consequences of delirium continue to afflict patients even after hospital discharge.